Repeatability coefficient and efficiency of micro tapping, test in seedlings of rubber tree - Gonçalves, Paulo de Souza; Rossetti, Adroaldo G.; Paiva, João Rodrigues de (Pesquisa Agropecuaria Brasileira, 2014)
The present study was carried out to determine the number of micro tapping test required to select seedlings of superior genotype in rubber tree (Hevea sp.) stock nursery. Three rounds of tests were carried out on half sib seedlings of RRIM 600 clone. Repeatibility coefficient (r) was estimated with two round and three round tests. For three round tests, the variances were estimated among plants in three different ways: a. analysis of variances that utilize one round test as replication (σ2p = 297.4232); b. analysis of variance isolating the effect of the test (σ2y = 300.5388) and c. by Vencovsky’s method (σ2g = 297.1777). The values of repeatibility coefficient estimated above were r = 0.7736, r = 0.7946 and r = 0.7731 respectivelly. These results show that the environmental variance within plant was low when compared with the variance among plants. The repeatibility coefficient for two round tests (r = 0.8317) was superior to three round tests, indicating that this value is inversely related to the number of tests utilized.